Penyuluhan Tanda Bahaya Kehamilan pada Ibu Hamil di Klinik Pratama - Hasmirah Hasmirah (Lembaga Pengembangan Kinerja Dosen, 2026)
Pregnancy is a physiological process that can develop into a pathological condition if early detection of pregnancy danger signs is not carried out. Lack of knowledge of pregnant women regarding danger signs, actions that must be taken, and the risks of not immediately seeking help can increase the incidence of pregnancy complications. This community service activity aims to increase the knowledge of pregnant women regarding pregnancy danger signs through health education activities. The activity was held on Wednesday, June 17, 2026 at 09.00 WITA at the Pratama Clinic area with a target of 17 pregnant women. The methods used included education using brochures, interactive lectures, discussions, and questions and answers. Before the education, an initial evaluation of the participants' knowledge was carried out, then a re-evaluation was carried out at the end of the activity. The evaluation results showed that before the education, most mothers only knew some of the pregnancy danger signs obtained from the KIA Handbook, but did not fully understand the actions to take when finding danger signs, how to prevent them, or the risks that could occur if not immediately addressed. After the education, there was an increase in participants' knowledge, where 15 mothers (88.2%) had a good level of knowledge and 2 mothers (11.8%) had a sufficient level of knowledge. Participants also showed high enthusiasm during the activity through active participation in discussions and asking various questions regarding their pregnancy conditions.